Implementation Of Islamic Religious Education Learning Programme Management - Ilmi, Irpan; Muliawati, Teti; Kurnia, Deni; Ruswandi, Uus (EDUTEC : Journal of Education And Technology, 2024)
This study aims to explore and analyze the implementation of Islamic Religious Education (PAI) learning program management at SMA Istiqamah Bandung using qualitative research methods. A qualitative approach was utilized to gain an in-depth understanding of how the PAI program management is implemented and its effectiveness in achieving the educational goals of Islamic religious education within the school. Data were collected through observations, interviews, and document analysis related to the PAI learning programs. The data analysis was conducted using an inductive approach to identify patterns, themes, and conclusions emerging from the qualitative data. The results indicate that the implementation of PAI learning program management at SMA Istiqamah Bandung is integrated with the curriculum, supported by adequate teacher resources, exhibits variations in teaching quality, and involves program expansion. This research aims to contribute to a deeper understanding of PAI learning program management implementation in Islamic High Schools and provide recommendations for the development of more effective and high-quality PAI learning programs in the future.